Modelling the role of credit rating agencies- Do they spark off a virtuous circle? - Christina E. Bannier; Marcel Tyrell (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2005)
In this paper, we propose a model of credit rating agencies using the global games framework to incorporate information and coordination problems. We introduce a refined utility function of a credit rating agency that, additional to reputation maximization, also embeds aspects of competition and feedback effects of the rating on the rated firms. Apart from hinting at explanations for several hypotheses with regard to agencies' optimal rating assessments, our model suggests that the existence of rating agencies may decrease the incidence of multiple equilibria. If investors have discretionary power over the precision of their private information, we can prove that public rating announcements and private information collection are complements rather than substitutes in order to secure uniqueness of equilibrium. In this respect, rating agencies may spark off a virtuous circle that increases the efficiency of the market outcome.
Keywords: G33; G14; D82; 330; information production; rating agencies; coordination problems; global game; Kreditwürdigkeit; Auskunftei; Asymmetrische Information; Lieferanten-Kunden-Beziehung; Spieltheorie; Gleichgewicht; Theorie; Ratingagentur